Coordination in Protected Forest Management in Indonesia: An Application of Soft Systems Methodology - DARMANTO DARMANTO (Jurnal Studi Pemerintahan, 2017)
Coordination is a very complex problem that has occurred in the management of protected forest in Indonesia.  The purpose of this study is to elucidate  how the Soft Systems Methodology (SSM) is used as a basis for rearranging coordination in  the  management of protected forest.  SSM demonstrates various aspects of coordination to be addressed and concrete steps that decision makers in the management of protected forest should make. Using the case example of protected forest management in Wonosobo Regency, Central Java, Indonesia, this study suggests that there are 9 steps to be considered in coordinating the management of protected forest. The findings of this study are relevant to decision makers in which the stages in SSM can assist decision makers to address problems in the coordination of protected forest management.